Sport and Its Relationship with Oncology in Future Primary Education Teachers - Lucía Melero García; Antonio Hernández Fernández; Eufrasio Pérez Navío (MDPI AG, 2020)
This essay is aimed at analyzing the existing relationships between oncological problems and sport in future primary education teachers. This relationship was validated and confirmed by realizing a factorial analysis using an ad hoc-created Likert scale. To come up to certain conclusions, a non-experimental, descriptive, explanatory and correlational investigation process was carried out. The instrument used to collect the data have been made through Likert scale, which was validated in contents and with an excellent Cronbach's alpha (0.952). The validity of construct was made with factorial analysis exploratory (KMO (0.722), Bartlett (0.000), determinant (3.266E−23)). Three different samples have been taken from 900 students (years 2017-2018-2019), being 896 subjects for research. Those persons were students from the fourth year of primary education degree at University of Jaen. The Kruskal-Wallis test allows us to keep the null hypothesis and make the P of Pearson. As a conclusion, we emphasize that there is a relationship between oncological problems and sport and future primary teachers should be informed about this relationship, as well as the importance of cancer and bones tumors and their relationship with sport, the media used to train in oncological problems may be less important.